The Effect of Using Schoology-Assisted Inquiry-Based Student Worksheet on Student Learning Outcomes - I Dewa Putu Nyeneng; Ni Made Dilla Agesta; Hervin Maulina (Universitas Lambung Mangkurat, 2021)
This study aimed to determine the effect of Schoology-assisted inquiry-based student worksheets on Newton's Law II material on students’ learning outcomes. The population in the study were all students of class X IPA. There are only two classes of X IPA at SMA Yadika Bandar Lampung, so the two classes were used as controlled and experimented classes. Controlled and experimented classes were chosen randomly, so it was determined that class X IPA 1 was the controlled class and X IPA 2 was the experimented class. The research method used was a quasi-experiment with a non-equivalent control group research design. The experimented class used a Schoology-assisted inquiry-based student worksheet, while the controlled class was given conventional learning. The two classes were given a different treatment, the experimented class implemented learning using guided inquiry-based worksheets, and the controlled class used a learning model that the physics teacher had implemented in the class. Before and after learning in both classes, five questions with HOTS level were given so that pretest and posttest data would be obtained as learning outcomes data. The data were analyzed by three tests: N-Gain, Independent Sample T-Test, and Effect Size Test. Based on the results of data analysis, there was an increase in cognitive learning outcomes in the controlled class, which was 0.21 included in the low category, while learning outcomes of the experimented class increase were 0.47 included in the moderate category. Besides that, the independent sample T-Test earned a value of sig. 2-tailed of 0.000, so it can be seen that there was an effect of using guided inquiry-based worksheets assisted by Schoology on Newton's Second Law towards students’ learning outcomes. In addition, the effect size test results showed a moderate category, so it can be concluded that Schoology-assisted inquiry-based student worksheet on Newton's second law material affects student learning outcomes. Based on the effect size test, the cohend's d value was 0.98 with a large category. This proved that the use of Schoology-assisted inquiry-based student worksheets had a moderate effect on students' cognitive learning outcomes.